Adaptive treatment workflow and dosimetric evaluation of intracranial fractionated stereotactic radiosurgery on a low-field magnetic resonance-linear accelerator - Karen Chin Snyder; Salim M. Siddiqui; Parag Parikh; Kundan Thind (Physics and Imaging in Radiation Oncology)
Background and Purpose: Online adaptive radiotherapy for fractionated intracranial stereotactic radiosurgery (FSRS) on a magnetic resonance linear accelerator (MR-L) has the potential to allow for real-time adjustments of anatomical changes during radiotherapy treatment. This study investigates the dosimetric improvements of an online-adaptive MR-L workflow and validates the dosimetry utilizing an MR-visible phantom. Methods and materials: Twenty-six cases previously treated with a conventional C-arm linear accelerator (CA-L) were replanned to determine optimal optimization constraints and objectives for achieving comparable MR-L plans. The optimization methodology was subsequently applied to simulate an online adaptive workflow on an MR phantom, incorporating target volumes from five previously treated patients that required offline adaptation. Plan quality and normal brain dose statistics were evaluated and compared to the offline adapted CA-L plans. Results: No significant difference was observed between the CA-L and MR-L target coverage. The normal brain dose for MR-L plans increased with target volume more rapidly than for CA-L plans. However, some outliers achieved equivalent normal brain doses, indicating potential benefits of MRIgRT for specific superficial volumes located in the frontal, occipital lobes, and cerebellum. End-to-end validation with simulated adaptive workflow on a MR phantom utilizing target volumes that previously required adaption showed acceptable difference of <2.5 % between measured and planned target dose. Conclusion: The study shows promising results for an online adaptive workflow for the treatment of intracranial FSRS on a low-field MR-L.